Prevalence and Severity of Plaque-Induced Gingivitis in A Sample of Adult Libyan Population - Samira Buzinin; Kholoud Ftis (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Plaque-induced gingivitis is the most common form of periodontal disease. Gingivitis prevalence in Libyan population in Tripoli city is not documented; therefore, the aim of this study was to evaluate the prevalence and severity of plaque-induced gingivitis among a sample of adult Libyan population. Methods. In this cross-sectional study Three hundred and twenty participants were recruited from routine dental patients attending the Periodontic clinic at Faculty of dentistry, University of Tripoli, Libya from October 2022 to May 2023. A clinical examination was performed by 2 dentists to measure the gingival and plaque indices of Löeand Silness for each subject. Results. The prevalence of gingivitis was 97.5% among adult subjects aged between 18-45 years old. Moreover, the mean gingival index was 1.08±0.52, which indicates a mild gingival inflammation. In fact, males showed more severe signs of gingival inflammation compared with females (p=0.029). In addition, the mean plaque index was 0.96±0.44, which indicates a good plaque status of the participants. However, males were more affected than females (p=0.003). Conclusion. The results of this study showed that plaque-biofilm accumulation is strongly associated with high prevalence of moderate to severe gingivitis among Libyan subjects.